2013
DOI: 10.4062/biomolther.2012.082
|View full text |Cite
|
Sign up to set email alerts
|

The Cholesterol-Binding Antibiotic Nystatin Induces Expression of Macrophage Inflammatory Protein-1 in Macrophages

Abstract: Nystatin, a polyene antifungal antibiotic, is a cholesterol sequestering agent. The antifungal agent alters composition of the plasma membrane of eukaryotic cells, whereas its effects on cells are poorly investigated. In the current study, we investigated the question of whether nystatin was able to induce expression of macrophage inflammatory protein-1 (MIP-1). THP-1 cells rarely express MIP-1α and MIP-1β, however, upon exposure to nystatin, significantly elevated expression of MIP-1α and MIP-1β was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Nystatin, a polyene antifungal antibiotic, is a cholesterol sequestering agent that alters the composition of the plasma membrane of eukaryotic cells [48]. However, its effect on cells is poorly investigated [48]. It was also found in our study that combination of lysine and nystatin also had an enhanced action, and this enhanced action was even stronger than the combination of AmB and lysine.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Nystatin, a polyene antifungal antibiotic, is a cholesterol sequestering agent that alters the composition of the plasma membrane of eukaryotic cells [48]. However, its effect on cells is poorly investigated [48]. It was also found in our study that combination of lysine and nystatin also had an enhanced action, and this enhanced action was even stronger than the combination of AmB and lysine.…”
Section: Discussionsupporting
confidence: 64%
“…The tube turbidity test indicated that there was a significant enhancement interaction between caspofungin or nystatin and lysine. Nystatin, a polyene antifungal antibiotic, is a cholesterol sequestering agent that alters the composition of the plasma membrane of eukaryotic cells [48]. However, its effect on cells is poorly investigated [48].…”
Section: Discussionmentioning
confidence: 99%
“…Nystatin has been used in experiments investigating the electrical properties of different tight epithelia, such as mammalian urinary bladder and colon epithelia, which characterized the conductances of the nystatin transmembrane pores for Na + , K + and Cl - [20,21]. In addition, it was observed that nystatin influences many mammalian cellular functions, among others the different intracellular signaling processes induced through the caveolae-associated proteins [22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescence analysis was conducted as described previously [30]. Briefly, Bart79I cells were grown on coverslips with indicated dose to 70 % confluency for 3 days.…”
Section: Immunofluorescencementioning
confidence: 99%